Família e orientação sexual: dificuldades na aceitação da homossexualidade masculina - De Lima Silva, Mônica Magrini; Frutuozo, Juliana Fernandes Furlan; Feijó, Marianne Ramos [UNESP]; Valerio, Nelson Iguimar; Chaves, Ulisses Herrera (Associacao Brasileira de Psicologia, 2015)
This article objectived to understand the living of men with homosexual orientation and the construction of meanings about homosexuality in their own families, through participant narratives. The participants this research were five male persons with homosexual orientation, resident and domiciled at São Paulo State's country, Brazil, who answered to a semi-structured interview and some questions for the Genogram's construction. The narratives were understood qualitatively through Systems Theory, also known as Complex Theory, and it implies considering relational, processual and contextual aspects for understanding human phenomena. The interviewed people reported tough situations related to a homosexuality experience, even at the moment which they reveal that situation for own families. This study, compatible with bibliographic data, showed that prejudices socially held, regarding several ways of individuals experience their own homosexuality, help to maintain the difficulties in the acceptance of male homosexuality, nowadays.
Family and sexual orientation: Difficulties in acceptance of male homosexuality
Keywords: Family; Homosexuality; Sexual orientation